Synthesis of Some of Azo, Triazines and Schiff Bases Compounds from 4-Aminohippuric Acid - Mohammed Sheat; Zenab Saeed; Mohammed Mohammed (College of Education for Pure Sciences, 2009)
Abstract Three new series of 4-aminohippuric acid ester derivatives have been prepared. The azo (4a-f) and azoamino (5a-e) compounds were prepared from electrophilic addition reaction of 4-diazonium chloride hippuric acid ester with phenols, aniline and secondary aliphatic amines, while Schiff bases(6a-g) were prepared from the condensation of 4-aminohippuric acid ester with aldehydes. The structural formula of the prepared compounds were confirmed by physical and spectral methods.